2022
DOI: 10.3390/gels8120781
|View full text |Cite
|
Sign up to set email alerts
|

Jetting Dynamics of Burning Gel Fuel Droplets

Abstract: Jetting in burning gel fuel droplets is an important process which, in addition to pure vaporization, enables the convective transport of unreacted fuel vapors from the droplet interior to the flame envelope. This aids in accelerating the fuel efflux and enhancing the mixing of the gas phase, which improves the droplet burn rates. In this study, Schlieren imaging was used to characterize different jetting dynamics that govern the combustion behavior of organic-gellant-laden ethanol gel fuel droplets. To initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The studies conducted by Sharma et al [ 22 ] provide insights into the jetting dynamics and their subsequent characterization. They employed dual mirror Z-type Schlieren imaging to visualize the jetting behavior of ethanol-based organic gel fuels and found that the jetting occurs via two modes, i.e., oscillatory, and isolated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies conducted by Sharma et al [ 22 ] provide insights into the jetting dynamics and their subsequent characterization. They employed dual mirror Z-type Schlieren imaging to visualize the jetting behavior of ethanol-based organic gel fuels and found that the jetting occurs via two modes, i.e., oscillatory, and isolated.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the relevant literature reveals that the combustion behavior of gel fuel has been analyzed either as a function of the initial droplet size and the ambient conditions [ 16 , 17 ] or the functional properties such as the parent fuel, the type of gellant (organic, inorganic, and cryogel) and their concentration [ 15 , 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 ]. While these studies have focused on determining droplet burn rates, a key mechanism that governs the combustion and jetting behavior in gel fuel droplets is the formation of a gellant shell, whose evolution during the droplet lifetime has been unexplored.…”
Section: Introductionmentioning
confidence: 99%